Procesy społeczno-polityczne zachodzące na Ukrainie w świetle publicystyki Mykoły Riabczuka - Pietnoczka, Paweł (Acta Polono-Ruthenica, 2007)
The aim of the article is to show the attitude of Mykola Ryabchuk towards the transformations in the Ukraine after the regaining of the independence in 1991. The publicist expresses severe criticism of the Ukrainian authorities for the way of pursueing interior and exterior politics. He accused them of corruption, chaos and lawlessness present in the everyday life. He also doesn’t spare the bitter words towards the society claiming that it couldn’t bring about the substitution of the ruling elites.